2020
DOI: 10.1002/eji.201948488
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of IL‐10 produced by B cells promotes protective immunity during persistent HCV infection in humanized mice

Abstract: Chronic HCV infection can lead to cirrhosis and is associated with increased mortality. Interleukin (IL)‐10‐producing B cells (B10 cells) are regulatory cells that suppress cellular immune responses. Here, we aimed to determine whether HCV induces B10 cells and assess the roles of the B10 cells during HCV infection. HCV‐induced B10 cells were enriched in CD19hi and CD1dhiCD5+ cell populations. HCV predominantly triggered the TLR2‐MyD88‐NF‐κB and AP‐1 signaling pathways to drive IL‐10 production by B cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…For instance, during murine cytomegalovirus and influenza virus infections, B cell-derived IL-10 restrains virus-specific CD8 + T cell responses ( 43 , 291 ). Breg-mediated inhibition of CD8 + T cell proliferation and IFN-γ production has also been demonstrated in patients infected with human immunodeficiency virus (HIV) ( 292 , 293 ) and hepatitis B virus ( 294 ) and in a humanized murine model of hepatitis C virus infection ( 295 ). There is evidence that Bregs can reduce CD8 + T cell responses indirectly through inhibition of CD4 + T cell help ( 296 ).…”
Section: Suppressive Mechanisms Of Bregs By Soluble Moleculesmentioning
confidence: 99%
“…For instance, during murine cytomegalovirus and influenza virus infections, B cell-derived IL-10 restrains virus-specific CD8 + T cell responses ( 43 , 291 ). Breg-mediated inhibition of CD8 + T cell proliferation and IFN-γ production has also been demonstrated in patients infected with human immunodeficiency virus (HIV) ( 292 , 293 ) and hepatitis B virus ( 294 ) and in a humanized murine model of hepatitis C virus infection ( 295 ). There is evidence that Bregs can reduce CD8 + T cell responses indirectly through inhibition of CD4 + T cell help ( 296 ).…”
Section: Suppressive Mechanisms Of Bregs By Soluble Moleculesmentioning
confidence: 99%
“…In HCC studies, enhanced expression of PD-1 has been found in a unique Breg cell subset ( 163 ); PD-1 blockade can be utilized to target Breg cells ( 164 ), indicating the importance of exploring specific Breg cell markers in CHB patients. In studies investigating the treatment of HCV infection and HCC, researchers have constructed the recombinant plasmid pcCD19scFv-IL10R to target mouse B10 cells and enhance the anti-HCV immune response or inhibit HCC growth in vivo ( 165 , 166 ). These findings might also provide some clues for targeting Breg cells during CHB infection.…”
Section: Target Breg Cellsmentioning
confidence: 99%
“…Similarly, IL-10-producing CD1d high CD5 + B cells (B10) were found in the spleen, suppressing CD4 + T cells, dendritic cells (DC), as well as monocytes thereby playing a protective role in a plethora of mouse models including experimental autoimmune encephalomyelitis (EAE) [ 982 , 983 ], lupus [ 984 ], myasthenia-gravis [ 985 ], collagen-induced arthritis [ 986 ], colitis [ 987 ], allergic inflammation [ 988 , 989 ] and contact hypersensitivity [ 990 ]. Furthermore, IL-10 derived from CD1d high CD5 + B cells also suppresses the immune response to Hepatitis-C virus by reducing cytotoxic T cell activity [ 991 ]. In spleen, also CD19 + TIM-1 + B cells were identified, suppressing CD4 + T cells [ 992 , 993 ].…”
Section: Introductionmentioning
confidence: 99%